KARAKTERISTIK ES KRIM SUSU KAMBING DENGAN PENAMBAHAN SARI JERUK SAMBAL (Citrus amblycarpa) - Dewi, Yohana Sutiknyawati Kusuma (Depertemen Teknologi Pertanian Universitas Hasanuddin, 2024)
Ice cream is a processed dairy product that enjoyed by various population. One source of animal milk that can be used in ice cream production is goat milk. However, goat milk has a drawback, that its strong aroma (goaty flavor), which makes it less appealing to the public. Efforts made to reduce the aroma of goat milk prengus are by adding Citrus amblycarpa juice. Citrus amblycarpa juice can be used as a substitute for synthetic flavoring. The purpose of this study is to develop the potential of Citrus amblycarpa juice as a natural flavoring in goat milk ice cream and obtain the best concentration of Citrus amblycarpa juice in goat milk ice cream formula. The study consists of six treatments, namely the addition of Citrus amblycarpa juice to the total ice cream formulation (0, 2.5, 5, 7.5, 10, and 12.5%). Each treatment is repeated four times. The observed parameters include physicochemical characteristics such a melting speed, total acidity, and total soluble solids. Sensory characteristics include color, taste, aroma, and texture. The best treatment is determined by the Syarifah effectiveness index. The results show that the addition of 2.5% Citrus amblycarpa juice to the total ice cream formulation is the best treatment, with physical and chemical characteristics of 29.25°Brix total soluble solids, 25.43 minutes melting speed, and 0.90% total acidity. For sensory characteristics, the color has a score of 3.50 (liked), aroma 3.53 (liked), taste 3.53 (liked), and texture 3.50 (liked).